The economic impact of the correct insulin injection technique associated with the use of 4 mm 32G needles in the treatment of patients with type 2 diabetes. (7th June 2018) - Ravasio, Roberto; Grassi, Giorgio
Objective: The purpose of the study is to estimate the financial impact on the Italian National Health Service of the use of BD Micro-Fine™ 4 mm 32G needles for insulin pens and of the BD Educational Starter Kit programme as compared to the use of longer pen needles, without the support of any educational programme. Methods: A budget impact model was developed to estimate the direct medical costs up to 12 months. The resource utilisation (insulin and complications associated with diabetes) was derived from literature. Only direct medical costs were considered. Ex-factory prices and National Tariffs were considered to estimate the costs of insulin and medical resource used to manage the complications associated with diabetes, respectively. The analysis was restricted to insulinised patients diagnosed with type 2 diabetes. Key variables were tested in the sensitivity analysis. Results: The cost per patient treated with BD needles presents a reduction of €32.08 of average annual cost (€690.02) compared to that associated with the patient treated with needles of other brands (€722.11). Given an increase in the percentage of use of BD needles that, compared to the base case, could involve 20%, 50% or 100% of patients, there would be a significant reduction in the expense incurred by the Italian National Health Service in the range of €2, 536, 710–€12, 683, 551. Conclusion: The use of the BD needles and the BD educational programme, as an alternative to the use of longer pen needles without the support of any educational programme, could represent an effective option to a low cost for the Italian National Health Service.